Aplicación de Algoritmos Genéticos para Localizar un Operador Logístico Maderero en la Localidad de Barrios Unidos, Bogotá D.C., Colombia - Polanco Tapia, César Augusto (Ingeniería, 2005)
This paper presents a genetic algorithm, to solve the problem of localization of a lumberman Logistical Operator, in the Barrios Unidos Locality (Bogotá D.C., Colombia). The used pattern of optimisation included the annual demand of 270 clients, the distance among the selected zones, as well as the costs of an only way of transport, besides the opening costs of the operator. In the genetic algorithm implementation, the crossing and mutation rates were varied, the number of generations, likewise five instances of problems were worked corresponding to the number of neighbourhoods (5, 10, 15, 20 and 26). These were kept in mind to summon the logistical operator.